THE ROLE OF SARCOPENIA INDEX AS A MARKER FOR MUSCULOSKELETAL HEALTH EVALUATION IN TYPE 2 DIABETES PATIENTS (Vietnam Journal of Community Medicine, 2026)
Objectives: This study aimed to investigate the association between sarcopenia index and muscle health indicators and to evaluate the incremental value of sarcopenia index in sarcopenia predictive models.Methods: This cross-sectional study included 74 patients with type 2 diabetes mellitus aged ≥ 50 years who attended the Outpatient Department of the University Medical Center Ho Chi Minh City - Campus 2 from May to October 2025. Sarcopenia was diagnosed using the AWGS (2025) criteria (low ASM/BMI and low handgrip strength). Sarcopenia index was calculated as serum creatinine × eGFRcys, with eGFRcys estimated by the CKD-EPI 2012 cystatin C-based equation. The diagnostic performance of the conventional model (model 1) and the sarcopenia index-augmented model (model 2) was assessed using ROC curves.Results: The prevalence of sarcopenia and severe sarcopenia was 41.9% and 12.2%, respectively. Sarcopenia index was positively correlated with ASM/BMI (r = 0.38, p < 0.001) and handgrip strength (r = 0.52, p < 0.001). Integrating sarcopenia index significantly improved diagnostic accuracy, with the AUC increasing from 0.8492 (model 1) to 0.8807 (model 2). Sarcopenia index was identified as an independent predictor (OR = 1.06; p = 0.018).Conclusion: The sarcopenia index is a useful biochemical marker that enhances diagnostic accuracy for sarcopenia when combined with traditional methods. It holds potential as a practical, low-cost screening tool in outpatient settings.
Keywords: Sarcopenia index, sarcopenia, type 2 diabetes mellitus, cystatin C.